Exercise as an antidepressant: exploring its therapeutic potential - Hwang, Dong-Joo; Koo, Jung-Hoon; Kim, Tae-Kyung; Jang, Yong-Chul; Hyun, Ah-Hyun; Yook, Jang-Soo; Yoon, Chang-Sun; Cho, Joon-Yong (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has increased the prevalence of depressive disorders worldwide, requiring alternative treatments beyond medication and psychotherapy. Exercise has positive effects on the brain; therefore, it has emerged as a promising therapeutic option for individuals with depression. Considerable research involving humans and animals offers compelling evidence to support the mental health benefits of physical activity or exercise mediated by the regulation of complex theoretical paradigms. However, challenges such as conducting long-term follow-up assessments and considering individual characteristics remain in human studies despite extensive efforts. While animal studies provide valuable insights into the potential benefits of exercise and its impact on outcomes related to depression and anxiety in rodents exposed to different stress paradigms, translating the findings to humans requires careful evaluation. More research is needed to establish precise exercise prescription guidelines and to better understand the complex relationship between exercise and depressive disorders. Therefore, this concise review explores the evidence supporting exercise intervention as an antidepressant treatment and its underlying mechanisms.